Impact of husband support on maternal psychological well-being during pregnancy: a systematic review - Fitriani Fitriani; Fitri Anita; Lilis Lilis (Edukasi Ilmiah Indonesia, 2025)
Introduction: Pregnancy is a vulnerable phase for the mother's mental health. Adequate husband support is believed to reduce the risk of psychological disorders such as depression, anxiety, and stress. This study aims to systematically examine the influence of husband support on the psychological well-being of mothers during pregnancy Research Methodology: This systematic study was conducted by searching scientific articles in the PubMed, Scopus, and PsycINFO databases from 2020 to 2025. The inclusion criteria included quantitative studies that evaluated the relationship between husband support and the psychological condition of pregnant women. Data from 18 eligible studies were analyzed narratively. Results: Most studies show that emotional, informative, and practical support from husbands is negatively correlated with maternal levels of depression, anxiety, and stress. Husbands who are actively involved in prenatal care contribute to the improvement of the mother's mental health. The lack of husband support has been shown to worsen psychological conditions during pregnancy. Conclusion: Husband's support has a significant impact on maintaining the psychological well-being of pregnant women. Family-based interventions and couples education programs can be effective strategies to improve husband support and maternal mental health during pregnancy